Comparison of Sputum Cytology with BronchoAlveolar Lavage Cytology in Diagnosis of Lung Cancer: A Hospital Based Study In BPKIHS - Adhikari, Milan; Karki, Smriti; Pradhan, Anju; Upadhyaya, Paricha (Journal of Nepalgunj Medical College, 2025)
Introduction: Lung cancer is one of the commonest cancers and its burden is increasing in developing countries as well. It has high mortality rate as most cases are diagnosed at late stages where there have very less therapeutic benefits. Early diagnosis of lung cancer can be done by cytology screening tools like Sputum and Bronchoalveolar Lavage Cytology study. Aims: To compare the diagnostic yield of Sputum cytology with Broncho-Alveolar Lavage cytology in diagnosing lung cancer by correlating with biopsy findings. Methods: This is a one-year hospital based prospective cross sectional study done at Department of Pathology, BPKIHS, Dharan. It included 34 cases subjected to Sputum and broncho-alveolar lavage cytology as well as Transbronchial biopsy. Diagnostic yield of Sputum and BAL cytology were calculated by correlating with biopsy findings. Results: Age of patients ranged from 29 to 84 years with near equal gender distribution. Biopsy was positive for lung cancer in 22 cases (65%). Sensitivity of Sputum and bronchoalveolar lavage cytology were calculated as 38.9% and 68.4% respectively. Cigarette smoking showed statistically significant correlation with Lung cancer. Most common cancer detected in biopsy was squamous cell carcinoma followed by Ad- enocarcinoma. Conclusion: Sputum and Bronchoalveolar Lavage cytology study can serve as initial screening tools for suspected lung cancer cases, especially in limited resources settings. However, the final confirmation has to be done by the gold standard histopathology study.